Pembinaan Dan Pengawasan Notaris Mantan Narapidana Oleh Majelis Pengawas Notaris Di Daerah Istimewa Yogyakarta - Satria Akbar Nagara (Officium Notarium, 2021)
This article examines the Guidance and Supervision of Notary Former Convicts by the Notary Supervisory Council based on UUJN and Permenkumham. The problem that is formulated is how to develop and supervise ex-convict Notaries by the Notary Supervisory Council in DIY, and what are the obstacles to fostering and supervising ex-convict Notaries by the Notary Supervisory Council in DIY. This type of research is normative which is supported by information from resource persons with a statutory approach and a conceptual approach. Legal materials were analyzed descriptively qualitatively. The results of this study conclude that the Guidance and Supervision carried out by the Notary Supervisory Council is guided by the UUJN and the RI Regulation of the Minister of Law and Human Rights No. 15 of 2020 while the Guidance and Supervision carried out by the Notary Supervisory Council to former Notary Convict members is an annual examination that has been regulated in the Notary Position Law. In the Picking Test of the Notary protocol, there has been no special attention or agenda in the regular monitoring of Notary Ex-Convicts and the obstacles that occur in the guidance and supervision, due to the Notary Supervisory Council which does not yet have special rules in carrying out its duties, thus triggering several subjective factors in viewing and assess the effectiveness of the guidance and supervision of the Notaries involvedKey Word: Supervisory Board of Notaries, Notaries, PrisonersAbstrakArtikel ini meneliti tentang Pembinaan dan Pengawasan Notaris Mantan Narapidana Oleh Majelis Pengawas Notaris berdasarkan UUJN dan Permenkumham. Masalah yang dirumuskan adalah bagaimana Pembinaan dan Pengawasan terhadap Notaris mantan narapidana oleh Majelis Pengawas Notaris di DIY, dan apa yang menjadi kendala pembinaan dan pengawasan notaris mantan narapidana oleh Majelis Pengawas Notaris di DIY. Jenis penelitian ini adalah Normatif yang didukung dari keterangan Narasumber dengan pendekatan perundang-undangan dan pendekatan konseptual. Bahan hukum dianalisis secara deskriptif kualitatif. Hasil penelitian tersebut menyimpulkan bahwa Pembinaan dan Pengawasan yang dilakukan Majelis Pengawas Notaris berpedoman UUJN dan Permenkumham RI No.15 Tahun 2020 sedangkan Pembinaan dan Pengawasan yang dilakukan oleh Majelis Pengawas Notaris kepada anggota Notaris Mantan Narapidana adalah pemeriksaan tahunan yang sudah diatur dalam Undang Undang Jabatan Notaris. Dalam Uji Petik protokol Notaris belum ada perhatian atau agenda khusus dalam monitoring secara berkala terhadap Notaris Mantan Narapidana dan Kendala yang terjadi dalam pembinaan dan pengawasan, disebabkan oleh Majelis Pengawas Notaris yang belum memiliki aturan khusus dalam menjalankan tugasnya sehingga memicu beberapa faktor yang bersifat subyektif dalam melihat dan menilai keefektifan pembinaan dan pengawasan terhadap Notaris yang terlibatKata Kunci: Majelis Pengawas Notaris, Notaris, Narapidana